PENGARUH KESADARAN, PELAYANAN FISKUS, DAN SANKSI TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Survey di PT Intikom Berlian Mustika) - Indri Febriani; Suparno (Jurnal Ilmiah Wahana Akuntansi, 2019)
This research aims to demonstrate empirically the effect of awareness of taxpayers, tax services and tax sanctions on the compliance of individual taxpayer. The sample in this research were employees who worked at PT Intikom Berlian Mustika. This research used primary data with distributing questionnaire. Questionnaires were distributed as many as 100 pieces to individual tax payer in PT Intikom Berlian Mustika. Research sampling were taken by simple random sampling. Statistical analysis using multiple linear regression. The results showed that tax awareness and sanctions significantly affected the compliance of individual taxpayers, while tax services did not affect the compliance of individual taxpayers at PT Intikom Berlian Mustika.